Markers of Systemic Inflammation in Acute Attacks of Ulcerative Colitis: What Level of C-reactive Protein Constitutes Severe Colitis?. (11th February 2022) - Croft, Anthony; Lord, Anton; Radford-Smith, Graham
Abstract: Background and Aims: The erythrocyte sedimentation rate [ESR] as a component of the Truelove and Witts Criteria [TWC] is the traditional inflammatory marker used for the assessment of ulcerative colitis [UC] activity. However, the C-reactive protein [CRP] is preferentially used in contemporary clinical practice. We aimed to determine the equivalent CRP cut-off for an ESR of  >30 mm/h in patients presenting with acute severe UC. Methods: Clinical and pathological data were prospectively collected from 163 presentations of severe UC. A CRP cut-off corresponding to an ESR of  >30 mm/h was determined using confusion matrices. A validation cohort of 128 presentations was prospectively collected and analysed. Results: A CRP cut-off of ≥12 mg/L generated an 85% positive predictive value [PPV] with a sensitivity of 95% and an accuracy of 82% for having a paired ESR of  >30 mm/h. There were no statistically significant differences between groups determined by the traditional ESR versus the new CRP-based criterion in the presenting faecal calprotectin, Mayo endoscopic subscore, or the rates of intravenous corticosteroid therapy failure and colectomy-by-discharge. Applying the CRP  ≥12 mg/L criterion to a validation cohort of 128 presentations generated a PPV of 83% and a sensitivity of 94%. Conclusions: The proposed CRP  ≥12 mg/L cut-off is an inclusive, sensitive, and very practical alternative to ESR as part of the TWC for defining UC presentation severity. It demonstrated similar performance characteristics to the classical ESR criterion when used for the assessment of acute UC disease activity. These findings were confirmed in a validation cohort.